MITRAL VALVE PROLAPSE AND SUDDEN CARDIAC DEATH: WHO IS IN THE RISK GROUP? - O. E. Shirobokikh; N. A. Bylova (Архивъ внутренней медицины)
Mitral valve prolapse (MVP) is a congenital heart disease, fairly widespread in the population (2-8%). It rarely has complications, but they are serious and include sudden cardiac death (SCD), risk of which rises twofold from 0.2-0.4% cases by MVP. Most deaths are observed among young healthy women. This work is a review of literature dedicated to connection between MVP and SCD designed to explore possible predicts of SCD within patients suffering from MVP and to determine the subset of patients. A conclusion has been made that the connection between MVP and SCD is realized through life-threatening ventricular arrhythmias (VT, VF). The most common site of arrhythmias origin is the inferobasal left ventricular wall. A high-risk subset of patients is determined as young adult women with a midsystolic click at auscultation, bileaflet involvement of the mitral valve, T-wave abnormalities on inferior leads (II, III, aVF) and frequent complex ventricular ectopic activity. Such patients require more intensive disease management of ventricular arrhythmias including consideration of surgical treatment.